Respiratory symptoms and chronic bronchitis in people with and without HIV infection. Issue 1 (6th September 2020) - Sabin, CA; Kunisaki, KM; Bagkeris, E; Post, FA; Sachikonye, M; Boffito, M; Anderson, J; Mallon, PWG; Williams, I; Vera, JH; Johnson, M; Babalis, D; et al.
Abstract : Objectives: High rates of respiratory symptoms and chronic bronchitis (CB) are reported in people with HIV infection (PWH). We investigated the prevalence of respiratory symptoms and CB in PWH and HIV‐negative people in the Pharmacokinetic and clinical Observations in PeoPle over fiftY (POPPY) study. Methods: Assessment of respiratory symptoms and CB was undertaken using the modified form of the St. George's Respiratory Questionnaire for chronic obstructive pulmonary disease (COPD). Univariate (χ 2 tests, Mann–Whitney U tests and Spearman's rank correlation) and multivariable (linear and logistic regression) analyses were performed to consider associations of respiratory symptoms with demographic, lifestyle and HIV‐related parameters, and with depressive symptoms and quality of life. Results: Among the 619 participants, respiratory Symptom scores were higher in older and younger PWH compared to older HIV‐negative people, with median (interquartile range) scores of 17.7 (6.2, 39.5), 17.5 (0.9, 30.0) and 9.0 (0.9, 17.5), respectively ( P = 0.0001); these differences remained significant after confounder adjustment. Sixty‐three participants (10.2%) met the criteria for CB [44 (14.0%) older PWH, 14 (9.2%) younger PWH, and five (3.3%) older HIV‐negative people; P = 0.002], with these differences also remaining after adjustment for confounding variables, particularly smoking status [older vs. younger PWH: odds ratio (OR) 4.48 (95% confidence interval (CI) 1.64, 12.30); P = 0.004; older PWH vs. HIV‐negative people: OR 4.53 (95% CI 1.12, 18.28); P = 0.03]. Respiratory symptoms and CB were both associated with greater depressive symptom scores and poorer quality of life. No strong associations were reported between CB and immune function, HIV RNA or previous diagnosis of any AIDS event. Conclusions: Respiratory symptoms and CB are more common in PWH than in demographically and lifestyle‐similar HIV‐negative people and are associated with poorer mental health and quality of life.